Face Validity of the Functional Assessment of Cancer Therapy-Breast Symptom Index (FACT- B) into Formal Arabic - Doumit, Myrna (2014)
Background: Breast cancer affects over one million women annually and is the most common global malignancy among women. Extensive improvements have taken place in the management of breast cancer in recent years and a higher percentage of women are cured from this disease. A proper assessment of the quality of life of women with breast cancer is an essential component in disease management. The Functional Assessment of Cancer Therapy- Breast Symptom Index has been commonly used and well-validated among English speaking populations as well as other populations. To date, no formal translation and evaluation of the Functional Assessment of Cancer Therapy-Breast System Index exists in Arabic. Therefore, this study intends to translate, adapt and face-validate the Functional Assessment of Cancer Therapy-Breast System Index into Arabic, specifically in the context of the Lebanese culture. Methods: We conducted forward and backward translation in Arabic, combined with face validity by clinicians. This was followed by pre-testing to ensure the instrument’s adequacy and cultural sensitivity conducted by the administration of face-to-face interviews with individual breast cancer patients (n=33) and two focus groups (4 women/group) to evaluate the relevance and appropriateness of each item and words used in the questionnaire. Results: Study results reinforced the value of the Arabic translated version of the Functional Assessment of Cancer Therapy-Breast System Index in capturing the quality of life of women with breast cancer in Lebanon. Conclusion: The instrument was perceived to be adequate, appropriate for use, culturally sensitive, simple as well as exhaustive. Suggestions have been made to enrich the instruments’ ability to incorporate other quality of life dimensions not captured, as well to enhance the cultural specificity of the Functional Assessment of Cancer Therapy-Breast System Index, when administered among Lebanese women diagnosed with breast cancer who are specifically beyond therapy.